Matrix-induced pre-strain and mineralization-dependent interfibrillar shear transfer enable 3D fibrillar deformation in a biogenic armour. (December 2019) - Wang, Yanhong; Zhang, Yi; Terrill, Nicholas J.; Barbieri, Ettore; Pugno, Nicola M.; Gupta, Himadri S.
Abstract: The cuticle of stomatopod is an example of a natural mineralized biomaterial, consisting of chitin, amorphous calcium carbonate and protein components with a multiscale hierarchical structure, and forms a protective shell with high impact resistance. At the ultrastructural level, cuticle mechanical functionality is enabled by the nanoscale architecture, wherein chitin fibrils are in intimate association with enveloping mineral and proteins. However, the interactions between these ultrastructural building blocks, and their coupled response to applied load, remain unclear. Here, we elucidate these interactions via synchrotron microbeam wide-angle X-ray diffraction combined with in situ tensile loading, to quantify the chitin crystallite structure of native cuticle – and after demineralization and deproteinization – as well as time-resolved changes in chitin fibril strain on macroscopic loading. We demonstrate chitin crystallite stabilization by mineral, seen via a compressive pre-strain of approximately 0.10% (chitin/protein fibre pre-stress of ∼20 MPa), which is lost on demineralization. Clear reductions of stiffness at the fibrillar-level following matrix digestion are linked to the change in the protein/matrix mechanical properties. Furthermore, both demineralization and deproteinization alter the 3D-pattern of deformation of the fibrillar network, with a non-symmetrical angular fibril strain induced by the chemical modifications, associated with loss of the load-transferring interfibrillar matrix. Our results demonstrate and quantify the critical role of interactions at the nanoscale (between chitin-protein and chitin-mineral) in enabling the molecular conformation and outstanding mechanical properties of cuticle, which will inform future design of hierarchical bioinspired composites. Statement of Significance: Chitinous biomaterials (e.g. arthropod cuticle) are widespread in nature and attracting attention for bioinspired design due to high impact resistance coupled with light weight. However, how the nanoscale interactions of the molecular building blocks – alpha-chitin, protein and calcium carbonate mineral – lead to these material properties is not clear. Here we used X-ray scattering to determine the cooperative interactions between chitin fibrils, protein matrix and biominerals, during tissue loading. We find that the chitin crystallite structure is stabilized by mineral nanoparticles, the protein phase prestresses chitin fibrils, and that chemical modification of the interfibrillar matrix significantly disrupts 2D mechanics of the microfibrillar chitin plywood network. These results will aid rational design of advanced chitin-based biomaterials with high impact resistance. Graphical abstract: Image, graphical abstract